Synthesis and Characterization Chitosan-ZnO nanoparticle and Its Application as Antibacterial Agent of Staphylococus aureus ATCC 25923 - Ahmad Fatoni; Ensiwi Munarsih; Kadek Asmadi; Nurlisa Hidayati (Science and Technology Indonesia, 2020)
The synthesis of modified chitosan has been studied. The aims of this research were modification of chitosan with ZnO nanoparticle to form chitosan-ZnO nanoparticle and its application as antibacterial agent of Staphylococus aureus. Characterization of modified chitosan was conducted using FTIR spectroscopy and X-Ray diffractometer. ZnO nanoparticle was synthesized by leaf extract of Sirih hijau (piper betle L) and zinc acetate dihydrate. Modified chitosan was synthesized by chitosan and ZnO nanoparticle. Modified chitosan solution can act as antibacterial agent with paper disk method. The result showed that chitosan can be modified with ZnO nanoparticle and detected at wave number of 3427 cm−1. The crystalline size of ZnO nanoparticle is 16.47 nm. The average inhibition zone of chitosan-ZnO nanoparticle at concentration 10.000, 5.000 and 2.500 ppm are 28.87 ± 0.4 ; 24.93 ± 0.15 and 19.35 ± 0.3 mm respectively.